A new family of multivariate slash distributions. Issue 7 (3rd April 2017) - Moradi, Z. Ghayour; Arashi, M.; Arslan, O.; Iranmanesh, Anis
ABSTRACT: In this article, a new form of multivariate slash distribution is introduced and some statistical properties are derived. In order to illustrate the advantage of this distribution over the existing generalized multivariate slash distribution in the literature, it is applied to a real data set.